From Modernism to Populism – art as a discursive mirror of the nation brand. (31st January 2018) - Rodner, Victoria; Kerrigan, Finola
Abstract : Purpose: The purpose of this paper is to examine the role played by the visual arts in expressing and shaping the nation brand. In doing so, it establishes the centrality of visual discourse in nation branding; illustrating that discursive strategies can directly alter the nation brand's perception. Design/methodology/approach: This single case study drawing on in-depth interviews, field observation and secondary/historical material, applies mediated discourse analysis and critical discourse analysis to capture a transitional period in the cultural policies and nation branding rhetoric across a time frame of 60 years. Findings: This study establishes the visual arts as a significant carrier of meaning, thus reflecting changes in the national discourse. This analysis illustrates that publicly supported visual arts can articulate policy aspirations and provide insight into the power of competing national discourse which co-exists, thereby shaping the internal and external nation brand. Research limitations/implications: The study focuses on the visual arts and the context of Venezuela. Future research could expand this to look at the visual arts in other national or regional contexts. Practical implications: The paper establishes visual art as central to expressing national identity and policy, and a tool for examination of national identity and policy. More broadly, the paper establishes public support for the (visual) arts as central to nation-branding projects providing insight for those engaged in such campaigns to prioritize arts funding. Originality/value: The authors' study indicates the marketing relevance of visualization of the nation through the arts and establishes the visual arts as a central tenant of the nation brand.